2023
DOI: 10.1097/prs.0000000000010572
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence: Singularity Approaches

Abstract: Summary: Artificial intelligence (AI) has been a disruptive technology within health care, from the development of simple care algorithms to complex deep-learning models. AI has the potential to reduce the burden of administrative tasks, advance clinical decision-making, and improve patient outcomes. Unlocking the full potential of AI requires the analysis of vast quantities of clinical information. Although AI holds tremendous promise, widespread adoption within plastic surgery remains limited. Understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Due to its incomplete mastery of guidelines and exceptional or speci c situations, the prevailing view of AI at present is that it can be a good assistant for doctors. 9,10,13,15 Singh and Nath noted in their review that AI is particularly bene cial in special cases, such as those of patients with rare diseases. 13 In surgeries where drug infusions are computer-assisted through closed-loop systems, the analysis of anesthesia depth and hemodynamic data has allowed the maintenance of vital parameters within narrower ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its incomplete mastery of guidelines and exceptional or speci c situations, the prevailing view of AI at present is that it can be a good assistant for doctors. 9,10,13,15 Singh and Nath noted in their review that AI is particularly bene cial in special cases, such as those of patients with rare diseases. 13 In surgeries where drug infusions are computer-assisted through closed-loop systems, the analysis of anesthesia depth and hemodynamic data has allowed the maintenance of vital parameters within narrower ranges.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 AI technology is now being frequently used in elds such as plastic surgery, oncology, pulmonology, cardiology, orthopedics, hepatology, and neurology. 9 Studies have shown that AI is particularly bene cial in imaging and diagnostic processes in these elds. AI-assisted systems approved by the US Food and Drug Administration have begun to be used to locate congenital heart pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…AI has the potential to automate and streamline healthcare administrative systems, reducing the burden on healthcare providers and optimizing processes [49]. In the emerging era, AI has exhibited a remarkable ability to efficiently carry out administrative functions on par with human capabilities [50]. While it cannot completely supplant the indispensable role of humans in healthcare management, AI presents an opportunity to optimize and streamline these operations, thereby assisting providers in their day-to-day administrative responsibilities.…”
Section: Redundant Administrative Tasksmentioning
confidence: 99%